Multiple mechanisms of selective attention: differential modulation of stimulus processing by attention to space or time. - Griffin, I; Miniussi, C; Nobre, A (2002)
Two studies compared the modulatory effects of orienting attention to spatial locations versus temporal intervals using event-related potentials (ERPs). In both experiments subjects performed attentional orienting tasks, which used identical stimuli in both spatial and temporal orienting conditions. The first experiment (N=16) used bilateral peripheral targets (7.5 degrees eccentricity) at two different time intervals (600, 1200 ms after cue onset). During spatial orienting a symbolic central cue predicted (75% probability) the spatial location (left, right) of the relevant target. No information was given about the probable target interval (short, long). In temporal orienting the cue predicted the target interval but not its location. Valid cueing produced significantly shorter reaction times in both the spatial and temporal orienting conditions. ERPs to identical, non-target stimulus arrays were analysed, to isolate endogenous attentional mechanisms. Spatial and temporal attention had distinct modulatory effects upon stimulus processing. Focused spatial attention affected the amplitude of early visual components. Modulation by temporal attention started later, and mainly affected potentials linked to decisions and responses. The second experiment (N=12) used unilateral target stimuli, and equated the probability of stimulus occurrence at short and long time intervals and at left or right of fixation. The results confirmed the distinct pattern of modulation of stimulus processing by spatial and temporal orienting. The optimisation of behaviour by attention can thus be achieved as a consequence of distinct modulatory processes, illustrating the flexibility of attentional functions in the human brain.